2020
DOI: 10.21203/rs.3.rs-40966/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Clients towards COVID-19 at Primary Healthcare Facilities in Rivers State, Nigeria

Abstract: Introduction: The outbreak of coronavirus (COVID-19) has impacted the lifestyles of people all over the globe as well as the economies of virtually every country. Several control measures have been introduced by both the State and Federal governments to fight the disease since its outbreak in Nigeria. In spite of all the measures, the disease is still ravaging the country. Therefore, this study investigated the knowledge, attitudes, and practices (KAP) of the clients who attended public primary healthcare faci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 9 publications
15
17
2
Order By: Relevance
“…The study revealed that a very signi cant proportion of the respondents used a face mask and this cuts all the participants irrespective of background characteristics. Our result might be in uenced by increased COVID-19 awareness among the Nigerian population [17], and as evident in this study. These ndings can be attributed to locations/a liation of the researchers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The study revealed that a very signi cant proportion of the respondents used a face mask and this cuts all the participants irrespective of background characteristics. Our result might be in uenced by increased COVID-19 awareness among the Nigerian population [17], and as evident in this study. These ndings can be attributed to locations/a liation of the researchers.…”
Section: Discussionsupporting
confidence: 53%
“…Most of the researchers reside in the Southern part of Nigeria where the literacy rate is high [18,19]. Study has shown that educational level in uences the community knowledge on coronavirus [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies [17,19]. The positive attitude towards the control and prevention of COVID-19 can also be explained by the actions and stringent control measures adopted by government and relevant agencies in fighting the disease, which include the closing of land and sea borders, airports, and all public spaces, such as open markets and schools [20]. The only significant factor associated with attitude was years of experience.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies [17,19]. The positive attitude towards the control and prevention of COVID-19 can also be explained by the actions and stringent control measures adopted by government and relevant agencies in ghting the disease, which include the closing of land and sea borders, airports, and all public spaces, such as open markets and schools [20].The only signi cant factor associated with attitude was years of experience. Year of experience was signi cantly related to both knowledge and attitude.…”
Section: Discussionsupporting
confidence: 90%